Starożytne miasta w basenie Morza Śródziemnego- w poszukiwaniu formy idealnej - Nowogórski, Przemysław (Saeculum Christianum. Pismo Historyczne, 2020)
Undoubtedly, one of the greatest achievements of antiquity in the Mediterranean basin is the origin and development of the city in a very broad sense; not only as the functional human settlement, but also the idea that found its place in philosophy. This article is a synthetic discussion of ancient Mediterranean urban planning in terms of its search of the ideal form of the city. Already in Mesopotamia and Egypt in the 4th - 3rd millennium BC they began to "experiment" with the layout of a functional and convenient city for its residents. However, only in the Greek and then Roman world did the ideal form find its full realization. It was then that the most representative examples of the ideal city were created.